Ruxandra Cesereanu, „Lumi de ficțiune, lumi de realitate”, București: Editura Tracus Arte, 2022, 354p. - PARASCHIV, Paul Mihai (Studia Universitatis Babeș-Bolyai Philologia, 2023)
Ruxandra Cesereanu’s 2022 book, Lumi de ficțiune, Lumi de realitate (Worlds of Fiction, Worlds of Reality), is a comprehensive and insightful exploration into various dimensions of literary fiction and its interplay with reality. Spanning across diverse literary traditions, genres, and historical contexts, Cesereanu delves into the works of notable authors like T.S. Eliot, C.S. Lewis, J.R.R. Tolkien, António Lobo Antunes, Roberto Bolaño, Will Self, Marie Darrieussecq, Leonid Dimov, Mircea Cărtărescu, Andrei Codrescu, Sei Shonagon, Franz Werfel, Ion D. Sîrbu, Patrick Modiano, Herta Müller, Elfriede Jelinek, and Ludmila Ulitskaya, providing readers with a rich and nuanced understanding of the complexities and intricacies of their narratives, along with a personal comparative style that reinvigorates these long-standing texts.